Yield and growth of dry bean as influenced by soil-water tension. I. Yield - Stone, Luís Fernando; Moreira, José Aloísio Alves; Silva, Silvando Carlos da (Pesquisa Agropecuaria Brasileira, 2014)
The effects of six irrigation treatments and two soil-water tension measurement depths (15 cm and 30 cm) on bean (Phaseolus vulgaris L.) yield were studied. The irrigation treatments consisted of irrigating when soil-water tension reached 125, 250, 375, 500, 625, and 750 mb. There was no significative difference in bean yield when irrigation scheduling was based on soil water tension measurements made at 15 cm or at 30 cm depths. After initial stand establishment, final plant population was not influenced by irrigations carried out at different soil-water tensions. On the other hand, the number of pods per plant, seeds per pod and grain yield decreased as the soil-water tension increased. The intensity of yield decrease depended on the environmental evaporative demand.